Detection of runaway electrons at the COMPASS tokamak using a Timepix3-based semiconductor detector. (1st February 2022) - ,; Kulkov, S.; Marcisovsky, M.; Svihra, P.; Tunkl, M.; van Beuzekom, M.; Caloud, J.; Cerovsky, J.; Ficker, O.; Macusova, E.; Mlynar, J.; Weinzettl, V.; et al.
Abstract: Runaway electrons are considered dangerous for the integrity of tokamak vacuum vessels. To secure the success of the future tokamak-based machines, reliable diagnostics and mitigation strategies are necessary. The COMPASS tokamak supported the research of runaway electron physics via regular experimental campaigns. During the last two experimental campaigns dedicated to runaway electrons, a semiconductor detector with a Timepix3 readout chip, Si sensor, and the SPIDR readout system was tested. Time evolution signals, energy measurements, and sensor snapshots collected with the Timepix3-based detector are presented.